Play Therapy in Children with Autism Diagnosis: An Investigation into the Trainers’ Opinions - Uzun, Meliha; Yılmaz, Baki (Türk Spor ve Egzersiz Dergisi, 2020)
This study aims to investigate the situations related to the effect of play therapy as a therapeutic recreational activity on individuals with autism. Accordingly, the opinions of 15 therapist trainers working at the Special Education and Rehabilitation Centers in Şırnak province were received. The research is based on a "phenomenology" model, which is one of the qualitative research patterns, and sampling was selected by using the "criterion sampling". In the research, a semi-structured interview technique was used as a data collection method. A personal information form and a semi-structured interview form consisting of five questions were applied to determine the opinions of the trainers about the effect of play therapy. The Nvivo program was used to evaluate the data obtained. The data were analyzed by the inductive analysis method. As a result of analyzing the research data, it was determined that the effect of play therapies for children with autism was in five categories such as “applied activities, effects, acquisitions, problems, and suggestions”. According to the research findings, it was observed in practices that children experienced various tantrums, attention deficit and communication gap, had anxiety in a crowded environment as well as were socially and psychologically affected and failed to adapt. Through the play therapy was a crucial element in the process of integrating into life by providing children with autism many positive acquisitions such as improving attention and concentration, ensuring cognitive, physical, emotional and multiple developments, acquiring communication skills, reducing problematic behavior, increasing focus, and socializing through an increase in social interaction features such as contributing to establish eye contact. In addition, it is very important to cooperate with families ensuring that they also actively participate in the education process to continue education in a coordinated manner.
Keywords: Autism; Play Therapy; Therapeutic Recreation